Integrated approaches to tackling health issues related to agri-food systems - Hung Nguyen-Viet; Grace, Delia; McDermott, J. (Springer, 2019)
Hunger, malnutrition, and poor health are declining but stubborn development challenges, even in countries where other aspects of development are moving forward. The world population has reached 7.6 billion people in 2018 but 815 million people suffer from chronic undernourishment. While overall and long-term trends are positive, progress is vulnerable to short term and regional setbacks. Paradoxically, over nutrition is becoming a more important global issue, as the rates of obesity and overweight populations increase; as for hunger, this tends to be associated with poverty. Unbalanced diets and inadequate nutrition now underlie a triple burden of undernutrition, overweight and obesity, and micronutrient deficiency. The importance of these challenges is emphasized by their prominence of Sustainable Development Goals relating to food security, health, environment, and gender.